2012
DOI: 10.1523/jneurosci.2765-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

5-HT7R/G12Signaling Regulates Neuronal Morphology and Function in an Age-Dependent Manner

Abstract: The common neurotransmitter serotonin controls different aspects of early neuronal differentiation, although the underlying mechanisms are poorly understood. Here we report that activation of the serotonin 5-HT 7 receptor promotes synaptogenesis and enhances synaptic activity in hippocampal neurons at early postnatal stages. An analysis of G␣ 12 -deficient mice reveals a critical role of G 12 -protein for 5-HT 7 receptor-mediated effects in neurons. In organotypic preparations from the hippocampus of juvenile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(161 citation statements)
references
References 78 publications
(101 reference statements)
12
147
1
1
Order By: Relevance
“…In our previous works, we have shown that RhoA can be activated by the 5-HT 7 R, although to a lesser extent than Cdc42 (Kvachnina et al, 2005;Kobe et al, 2012). In contrast to Cdc42, which propels cell movement by promoting cellular extension and spreading, RhoA mediates detachment and cell rounding through regulation of actin filament rearrangements (Graness et al, 2006;Hall, 1994Hall, , 1998Sepp and Auld, 2003;Swetman et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our previous works, we have shown that RhoA can be activated by the 5-HT 7 R, although to a lesser extent than Cdc42 (Kvachnina et al, 2005;Kobe et al, 2012). In contrast to Cdc42, which propels cell movement by promoting cellular extension and spreading, RhoA mediates detachment and cell rounding through regulation of actin filament rearrangements (Graness et al, 2006;Hall, 1994Hall, , 1998Sepp and Auld, 2003;Swetman et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…In this context, members of the Rho family of small GTPases, whose most prominent feature is the regulation of the actin cytoskeleton (Hall, 1994;Machesky and Hall, 1997;Norman et al, 1994) represent key players that are crucially involved in the regulation of dendritic cell migratory properties (Benvenuti et al, 2004;Harada et al, 2012;Lammermann et al, 2009;Ocana-Morgner et al, 2011). Our previous data have indicated that, in neurons, actin cytoskeleton rearrangements can be regulated by 5-HT 7 R through the G 12 protein-mediated activation of the small GTPase Cdc42 (Kobe et al, 2012;Kvachnina et al, 2005;Nobes and Hall, 1995a,b). We have also demonstrated a high basal activity of 5-HT 7 R towards Cdc42 signaling in neuronal cells (Kvachnina et al, 2005), suggesting that both basal activity and agonist-mediated stimulation of the 5-HT 7 R-Cdc42 signaling pathway might contribute to morphological rearrangements of cells.…”
Section: Discussionmentioning
confidence: 98%
“…5-HT7R is considered to play an important role in the maintenance and regulation of balance between potentiation and depression of hippocampal networks (Kobe et al, 2012 andClark andNormann, 2008). In particular, it has been shown that the stimulation of 5-HT7R results in a marked enhancement of spontaneous neuronal activity leading to saturation of LTP and thus preventing further potentiation.…”
Section: -Ht7r Modulates Synaptic Plasticity At Parallel Fiber-purkimentioning
confidence: 99%
“…8B). To study the functional implication of 5-HT 1A -5-HT 7 heterodimerization, we developed short interfering RNAs (siRNAs) to specifically knockdown the endogenously expressed 5-HT 7 receptor (Kobe et al, 2012) (supplementary material Fig. S5A).…”
Section: Analysis Of Receptor Heteromerization By Acceptor Photobleacmentioning
confidence: 99%